2021
DOI: 10.3390/foods10102435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Hydrostatic Pressure on the Extractability and Bioaccessibility of Carotenoids and Their Esters from Papaya (Carica papaya L.) and Its Impact on Tissue Microstructure

Abstract: High hydrostatic pressure (HHP) is a non-thermal technology widely used in the industry to extend food shelf-life and it has been proven to enhance the extractability of secondary metabolites, such as carotenoids, in plant foods. In this study, fresh-cut papaya pulp of varieties (Sweet Mary, Alicia and Eksotika) from the Canary Islands (Spain) were submitted to the HHP process (pressure: 100, 350 and 600 MPa; time: come-up time (CUT) and 5 min) to evaluate, for the first time, individual carotenoid and caroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 56 publications
0
10
0
6
Order By: Relevance
“…However, significant differences (p < 0.05) were observed for its major xanthophyll ester, (all-E)-βcryptoxanthin laurate, showing higher bioaccessibility in the O/W sunflower emulsion (7.2 ± 0.9%) than in the O/W soybean emulsion (3.5 ± 0.1%). With respect to (all-E)-βcarotene, higher bioaccessibility was observed in both the O/W soybean (17.9 ± 0.7%) and sunflower (18.4 ± 0.4%) emulsions compared to its bioaccessibility in a previous study of the in vitro digestion of un-encapsulated extracts [7]. (all-E)-Lycopene showed the highest bioaccessibility among all the carotenoids of the extracts of papaya encapsulated by O/W emulsions.…”
Section: Carotenoid Stability and Bioaccessibility In O/w Microemulsionsmentioning
confidence: 67%
See 3 more Smart Citations
“…However, significant differences (p < 0.05) were observed for its major xanthophyll ester, (all-E)-βcryptoxanthin laurate, showing higher bioaccessibility in the O/W sunflower emulsion (7.2 ± 0.9%) than in the O/W soybean emulsion (3.5 ± 0.1%). With respect to (all-E)-βcarotene, higher bioaccessibility was observed in both the O/W soybean (17.9 ± 0.7%) and sunflower (18.4 ± 0.4%) emulsions compared to its bioaccessibility in a previous study of the in vitro digestion of un-encapsulated extracts [7]. (all-E)-Lycopene showed the highest bioaccessibility among all the carotenoids of the extracts of papaya encapsulated by O/W emulsions.…”
Section: Carotenoid Stability and Bioaccessibility In O/w Microemulsionsmentioning
confidence: 67%
“…However, most of them present low availability (5-30%) compared to other food phytochemicals [6]. A previous study reported by our group [7] showed low bioaccessibility of the individual carotenoids from papaya pulp (Sweet Mary variety) exposed to the high hydrostatic pressure (HHP) process. In that work, the bioaccessibility values reported for β-cryptoxanthin, β-cryptoxanthin laurate, β-carotene, and lycopene ranged from 0 to 3% in the control and HHP-treated samples, respectively, indicating that there was no improvement in carotenoid bioaccessibility due to this process.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…It was also suggested that HPP can improve bioactive compound extractability due to changes in the food structure of the product. In this context, Lara-Abia et al [ 11 ] evaluated the impact of HPP on extracting individual carotenoid and carotenoid ester from papaya and assessed their bioaccessibility using an in vitro simulated gastrointestinal digestion assay. The results showed a high carotenoid stability but very low bioaccessibility.…”
mentioning
confidence: 99%